Challenges faced by postgraduate students to become self-directed learners / Farhana Wahab - Wahab, Farhana (2013)
This study seeks to identify the challenges that the postgraduate Masters students faced to become self-directed learners. The challenges are determined based on the factors that influence the development of students’ self-direction, namely the support provided by the lecturers, peers and library; the students’ personal attitudes; as well as the students’ knowledge and academic skills. It also aims to compare the challenges that full-time and part-time students encounter, in order to provide broader view of this matter and to help both authorities and students to take appropriate actions in addressing the problems. The population of the study is postgraduate students in Selangor while the samples are Masters students of a local university. A total of 121 questionnaires were distributed to the students but only 56 were returned. The findings suggest that the students faced challenges pertaining to the lack of support provided by the library, poor time management, motivation, ability to think critically, and lack of academic skills in reading journals and writing critically. As for the comparison of the challenges faced by the full-time and part-time students, 9 significant differences are detected which revolve around their perception of the support provided by the library and peers, the use of collaborative learning, dependency on the lecturers, and students’ participation in classroom. Based on the findings, actions should be taken by various parties such as the library, students and lecturers in order to overcome the problems. The librarians should improve their service to the students and add more materials in the database; the students should improve their academic skills and learning attitudes; while the lecturers ought to revise their teaching methods to ensure that they are suitable for providing mediums for the students to enhance their knowledge and skills, and work collaboratively with each other.